Exploring the relationships of financial literacy and financial behaviour with Health-Related Quality of Life (HRQOL) among the low-income working population in Malaysia during the COVID-19 pandemic - Sabri, Mohamad Fazli; Said, Mas Ayu; Magli, Amirah Shazana; Tan, Maw Pin; Rizal, Hussein; Thangiah, Nithiah; Ithnin, Muslimah; Abdul Majid, Hazreen; Ismail, Rozmi; Tin, Tin Su; Abdul Rahim, Husniyah (Multidisciplinary Digital Publishing Institute, 2022)
This cross-sectional study examined the relationships of financial literacy (FL) and financial behaviour (FB) with health-related quality of life (HRQOL) during the COVID-19 pandemic among low-income working population (20–60 years old) in Malaysia. A self-administered questionnaire survey was used with HRQOL data were gathered using the EuroQol 5-Dimension 5-Level (EQ-5D-5L) tool. A generalised linear model was employed to examine the hypothesised relationships between the constructs. From 1186 respondents, the majority were employed (73.9%), had a monthly household income of less than RM 2500 (74.5%), and did not have any chronic medical conditions (74.5%). The mean (SD) values of FL, FB, and EQ-5D-5L were 5.95 (1.48), 22.08 (4.79), and 0.96 (0.10), respectively. The results of the adjusted model revealed lower age group, Malay ethnicity, Indian ethnicity, and increased FB score as significant determinants of higher EQ-5D-5L scores. With the addition of the chronic medical condition factor into the saturated model, the lower age group, ethnicity, and no chronic medical condition were significant determinants of higher HRQOL. The effects of FB on QOL were confounded by chronic diseases, implying that interventions that focus on improving FB for those with chronic medical condition may help to improve the QOL among the low-income working population.